ANTARA PENDIDIKAN DAN KEKERASAN TERHADAP ANAK DI LINGKUNGAN SEKOLAH - Muhammad Misdar (Conciencia, 2016)
Factually, the school is the place to gain knowledge, in schools that also students or students can develop their talents, interests and all potentials. But frequent frictions so that ideally the school should be a place to develop the potential of students, turning into a container of violence against children. The next issue is whether all elements in the school environment or do not realize that in the school there is violence in schools. From there need to be no understanding kekeraan revitalization of the students in the school environment, so that any form of violence against the students can not be allowed in the school environment. There are several reasons the appearance of school violence, such as Fator educational process, as it is known that the learning process in the school environment is not entirely stable, due to the curriculum, educators condition, input protégé. While the advances in information technology and its use of massive school environment has dragged the psychological condition of students become alienated from the conditions of learning the truth, Similarly, the mental state and behavior of teachers that would hetrogen and sometimes-kaadang unstable, these conditions when in direct contact with students certainly have an impact on friction, friction least psychologically, on the other hand the values ​​of care that teachers do, indeed felt by parents, especially parents who are educators began to dim in the educational process. What is mentioned above, is not to be something permanent to live in the school of environmental, efforts to minimize it always becomes a necessity, because the condition was raw, but must be done consciously by all parties, educators, students and parents. Therefore, give a space of freedom for students to learn authoritatively be one alaternatif, which is accompanied by the planting of self-efficacy of teachers permanently in implementing education, so that all will have an impact on teachers' pedagogical abilities.